Placing, displacing, replacing the sacred: science, religion, and spirituality - Rolston, Holmes, 1932-2025, author; Equinox Publishing Group, publisher (Colorado State University. Libraries, 2015)
This is a reply to a target article in this issue by Lisa Sideris, "Science as Sacred Myth? Ecospirituality in the Anthropcene Age." Lisa Sideris is right on target, concerned about scientism. Big-history-epic-of-evolution accounts, such as Brian Swimme and Mary Evelyn Tucker in their Journey of the Universe direct us to awe, inviting us to see better what is going on at our local, personal scales by including microscales, ecosystemic, evolutionary, geological, and astronomical scales. Against local myths, a scientific account ("myth"?) can be definitive. Any contemporary culture must "incorporate" vast amounts of science. Journey of the Universe is an excellent video, though it would be better if it recognized that some native accounts are wrong.
Keywords: Sideris, Lisa; Swimme, Brian; Tucker, Mary Evelyn; journey of the universe; scientism; evolutionary natural history; cosmology; science and religion; myth; superstition